Epigenetics of Ageing and Psychiatric Disorders - Cezar-Ivan Colită; Ion Udristoiu; Diana-Larisa Ancuta; Dirk M Hermann; Daniela Colita; Eugen Colita; Daniela Glavan; Aurel Popa-Wagner (Journal of Integrative Neuroscience, 2024)
Both classic epigenetic modifications and microRNAs can impact a range of bodily processes, from metabolism to brain function, and may contribute to the development of diseases such as cancer, cardiovascular disorders, and psychiatric disorders. Numerous studies suggest a connection between epigenetic changes and mood disorders. In this study, we performed a comprehensive search using PubMed and Google for the terms “epigenetics”, “ageing”, “miRNA”, “schizophrenia”, and “mood disorders” in the titles and abstracts of articles. Epigenetic changes during early life may play a crucial role in triggering severe mental disorders and shaping their clinical trajectory. Although these alterations can take place at any age, their impact may not be immediately evident or observable until later in life. Epigenetic modifications play a crucial role in the ageing process and challenge the prevailing belief that mutations are the primary driver of ageing. However, it is plausible that these epigenetic changes are a consequence of the disorder rather than its root cause. Moreover, both the disorder and the epigenetic alterations may be influenced by shared environmental or genetic factors. In the near future, we might be able to replace chronological age with biological age, based on the epigenetic clock, with the promise of providing greater therapeutic benefits. A wide range of epigenetic drugs are currently under development at various stages. Although their full effectiveness is yet to be realized, they show great potential in the treatment of cancer, psychiatric disorders, and other complex diseases.